Isoalantolactone inhibits IKKβ kinase activity to interrupt the NF‐κB/COX‐2‐mediated signaling cascade and induces apoptosis regulated by the mitochondrial translocation of cofilin in glioblastoma. (10th February 2019) - Xing, Jin‐Shan; Wang, Xun; Lan, Yu‐Long; Lou, Jia‐Cheng; Ma, Binbin; Zhu, Tingzhun; Zhang, Hongqiang; Wang, Dongsheng; Yu, Zhikuan; Yuan, Zhongbo; Li, Xin‐Yu; Zhang, Bo
Abstract: Isoalantolactone (IATL), a sesquiterpene lactone compound, possesses many pharmacological and biological activities, but its role in glioblastoma (GBM) treatment is still unknown. The aim of the current study was to investigate the antiglioma effects of IATL and to explore the underlying molecular mechanisms. In the current study, the biological functions of IATL were examined by MTT, cell migration, colony formation, and cell apoptosis assays. Confocal immunofluorescence techniques, chromatin immunoprecipitation, and pull‐down assays were used to explore the precise underlying molecular mechanisms. To examine IATL activity and the molecular mechanisms by which it inhibits glioma growth in vivo, we used a xenograft tumor mouse model. Furthermore, Western blotting was used to confirm the changes in protein expression after IATL treatment. According to the results, IATL inhibited IKKβ phosphorylation, thus inhibiting both the binding of NF‐κB to the cyclooxygenase 2 (COX‐2) promoter and the recruitment of p300 and eventually inhibiting COX‐2 expression. In addition, IATL induced glioma cell apoptosis by promoting the conversion of F‐actin to G‐actin, which in turn activates the cytochrome c (Cyt c) and caspase‐dependent apoptotic pathways. In the animal experiments, IATL reduced the size and weight of glioma tumors in xenograft mice and inhibited the expression of COX‐2 and phosphorylated NF‐κB p65 in the transplanted tumors. In conclusion, the current study indicated that IATL inhibited the expression of COX‐2 through the NF‐κB signaling pathway and induced the apoptosis of glioma cells by increasing actin transformation. These results suggested that IATL could be greatly effective in GBM treatment. Abstract : Isoalantolactone (IATL) could effectively inhibit the proliferation of glioblastoma (GBM) cells and induce apoptosis by inducing cofilin and G‐actin translocation to the mitochondrial inner membrane. Intriguingly, IATL can target the IκB kinase β cascade signaling pathway and block the NF‐κB signaling pathway. These findings provide the basis for the clinical use of IATL and provide evidence supporting the further development of potential antitumor drugs.